Relationship between eating habits and triggering factors of migraine crises (Research, Society and Development, 2020)
This article aimed to analyze, through an integrative review, the relationship between eating habits and the triggers of migraine attacks. We searched for articles published in the last five years in national and international journals in the following electronic databases: SCIELO, Pubmed and LILACS, using the following descriptors: migraine, diet and triggering factors. The search resulted in 38 articles, of which seven were selected, after applying the inclusion and exclusion criteria, for analysis, interpretation and discussion. Of these studies, the quantitative research method observed was the observational cross-sectional design. It was observed that in the studies analyzed described, a large part of the increase in the incidence of migraine in people is basically related to the poor quality of their eating habits and lifestyle. It is understood that there is a relationship between eating habits and migraine attacks. However, it is necessary to have a qualified professional to carry out a nutritional assessment, aiming to balance the nutritional status before the individualities of each carrier.